Economic implications and quality assessment of biochar-enriched potting media: A case study on Terminalia bellerica seedlings - Sherke, Pankaj; Ramanan S, Suresh; Kumar, Naresh; Gupta, Ashta; A, Arunachalam (Indian Journal of Agroforestry, 2025)
Terminalia bellerica Roxb. is a tall, deciduous, indigenous tree species widely recognized for its medicinal value and is a key ingredient in Triphala, a traditional Ayurvedic formulation that also includes Terminalia chebula and Emblica officinalis. Adapted to specific climatic conditions, it plays an important role in local economies, highlighting its ecological and economic significance in India’s forest ecosystems. Among the treatments, conventional media (T1: soil + sand + FYM, 1:1:1) was compared with various biochar-based combinations, particularly T2 (soil + biochar + FYM, 1:1:1). Biochar, known for its low bulk density, porous structure, and nutrient-retention capacity, significantly reduced the filled polybag weight and enhanced water retention. Water retention analysis across all treatments demonstrated the effectiveness of biochar as a sustainable nursery media amendment. The study aimed to evaluate the effect of biochar as a substrate on the growth and development of selected tree species seedlings and to assess the influence of varying biochar proportions on seedling quality parameters.